2016
DOI: 10.1021/acsmedchemlett.6b00248
|View full text |Cite
|
Sign up to set email alerts
|

New Series of BPL Inhibitors To Probe the Ribose-Binding Pocket of Staphylococcus aureus Biotin Protein Ligase

Abstract: Replacing the labile adenosinyl-substituted phosphoanhydride of biotinyl-5′-AMP with a N1-benzyl substituted 1,2,3-triazole gave a new truncated series of inhibitors of Staphylococcus aureus biotin protein ligase (SaBPL). The benzyl group presents to the ribose-binding pocket of SaBPL based on in silico docking. Halogenated benzyl derivatives (12t, 12u, 12w, and 12x) proved to be the most potent inhibitors of SaBPL. These derivatives inhibited the growth of S. aureus ATCC49775 and displayed low cytotoxicity ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 22 publications
1
27
0
2
Order By: Relevance
“…12 Bisubstrate inhibitors have been described for the structurally related BPL from Staphylococcus aureus including alkylphosphates, 13 β-ketophosphonates, 14 and triazole nucleosides, 15,16 as well as analogues wherein the adenosine nucleobase was replaced with benzoxazoline 17,18 and aryl moieties. 19 We have reported 5′-[N-(D-biotinoyl)sulfamoyl]amino-5′-deoxyadenosine (Bio-AMS, 1, Figure 1A) is a potent subnanomolar bisubstrate inhibitor of the mycobacterial biotin protein ligase (MtBPL). 20 Bio-AMS possesses excellent antitubercular activity against Mtb H37Rv and MDR/XDR-TB strains with minimum inhibitory concentrations (MICs) ranging from 0.16 to 0.625 μM and is not affected by changes to the primary carbon source.…”
mentioning
confidence: 99%
“…12 Bisubstrate inhibitors have been described for the structurally related BPL from Staphylococcus aureus including alkylphosphates, 13 β-ketophosphonates, 14 and triazole nucleosides, 15,16 as well as analogues wherein the adenosine nucleobase was replaced with benzoxazoline 17,18 and aryl moieties. 19 We have reported 5′-[N-(D-biotinoyl)sulfamoyl]amino-5′-deoxyadenosine (Bio-AMS, 1, Figure 1A) is a potent subnanomolar bisubstrate inhibitor of the mycobacterial biotin protein ligase (MtBPL). 20 Bio-AMS possesses excellent antitubercular activity against Mtb H37Rv and MDR/XDR-TB strains with minimum inhibitory concentrations (MICs) ranging from 0.16 to 0.625 μM and is not affected by changes to the primary carbon source.…”
mentioning
confidence: 99%
“…Previous reports indicated that suppressors of essential metabolic enzymes could be developed as new classes of antibiotics. For example, BPLs have been studied for a few years as drug targets for new antibiotics ( Costa et al, 2012 ; Feng et al, 2016a , b ). Studies have shown that biotin analogs, as inhibitors of BPL, have significant antibacterial activity against M. tuberculosis ( Duckworth et al, 2011 ; Bockman et al, 2015 ), E. coli ( Xu and Beckett, 1994 ; Brown and Beckett, 2005 ), S. aureus ( Costa et al, 2012 ; Pendini et al, 2013 ; Paparella et al, 2014 ), and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Three lines of evidence were consistent with BASA acting through direct binding to the BPL target. Firstly, the compound showed reduced antibacterial activity against a strain of S. aureus engineered to overexpress SaBPL [19]. The increased concentration of recombinant BPL in the bacteria elevated the MIC by eight-fold over an isotypic control strain ( Figure S5A).…”
Section: Mechanism Of Action Of Basamentioning
confidence: 99%
“…ACC and BPL have been identified as essential gene products for growth in genetic knockout studies performed on S. aureus [9][10][11][12] and, consequently, have been the targets of drug discovery programs. The antibacterial efficacy of ACC inhibitors has been demonstrated in vivo (reviewed in [13,14]) and BPL inhibitors have shown efficacy in vitro against S. aureus and M. tuberculosis [15][16][17][18][19]. Whilst dispensable for growth in culture, PC has been shown to be an important virulence factor in bacteremia models in mice and nematodes [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation